Reliability and validity of the Turkish version of the short food literacy questionnaire among university students - Durmus, Hasan; Gökler, Mehmet Enes; Havlioğlu, Suzan (Progress in Nutrition, 2019)
The aim of this study was translating and adapting the SFLQ to Turkish and evaluating the validity and reliability for adults in Turkey. In accordance with the purpose of the study, a 2-part questionnaire was prepared. The first part focused on the sociodemographic characteristics, including age, sex, and questions that determine food label reading habits. The second part consisted of the Newest Vital Sign (NVS) test, Turkey Health Literacy SCALE-32 (TSOY-32) and Short Food Literacy Questionnaire (SFLQ). The construct validity of the SLFQ was assessed using factor analysis. The Kaiser-Meyer-Olkin (KMO) measure of sampling adequacy was 0.811. Bartlett’s test of sphericity was significant (X2=841.958, df=66; p